Phytoremediation potential of Avicennia marina, Rhizophora mucronata, and Bruguiera gymnorrhiza in lead (Pb) contaminated urban coastal areas - Permatasari, Fina Dwi; Aditya, Haidar Fari; Mindari, Wanti (Universitas Lancang Kuning, 2025)
Heavy metal contamination in urban coastal areas poses a serious environmental threat, with lead (Pb) being one of the most persistent and hazardous pollutants. Mangrove forests, which act as natural buffers between land and sea, have the potential to mitigate heavy metal pollution through phytoremediation. This study evaluates the phytoremediation potential of three mangrove species—Avicennia marina, Rhizophora mucronata, and Bruguiera gymnorrhiza—in lead-contaminated coastal areas of Wonorejo and Gunung Anyar, Surabaya, Indonesia. Sediment, root, and leaf samples were collected using a survey method and purposive random sampling. Physiochemical analysis included soil texture, pH, electrical conductivity (EC), and Pb concentration. Pb levels in Gunung Anyar sediments reached 12.0 ppm, higher than Wonorejo’s 4.05 ppm. A. marina exhibited the highest Pb accumulation, with a bioconcentration factor (BCF) of 8.85 in roots and 6.97 in leaves. R. mucronata had a BCF of 5.75 in roots and 2.09 in leaves, while B. gymnorrhiza demonstrated a root BCF of 28.8 and leaf BCF of 28.4. Translocation factor (TF) analysis revealed that A. marina had the highest TF (1.27), indicating phytostabilization as its primary mechanism. Meanwhile, R. mucronata and B. gymnorrhiza exhibited phytoextraction characteristics due to higher metal translocation efficiency. These findings highlight the distinct phytoremediation strategies among species.